Demystifying scholarly metrics a practical guide - Vinyard, Marc W.; Colvin, Jaimie Beth (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"Demystifying Scholarly Metrics gives librarians and faculty the confidence to navigate the maze of scholarly metrics, identify quality journals in which to publish, and measure the impact of scholarly works"--Provided by publisher.
Why are you reading this book? -- You know more than you think -- H-indexes, altmetrics, and impact factors-oh my! -- Metrics for all kinds of scholars -- Open access : the good, the bad, and the ugly -- Finding a journal that's the right fit -- Publish, don't perish! : applying what you've learned -- Developing or finding metrics services at your hibrary -- Avoid drowning in a sea of scholarly metrics : how to stay current.
Includes bibliographical references and index.
Keywords: Bibliometrics -- Handbooks, manuals, etc; Scholarly publishing -- Evaluation; Research -- Evaluation -- Statistical methods